Efektifitas Strategi Thinking Aloud Pair Problem Solving (TAPPS) dengan Pendekatan Open-Ended pada Siswa SMP - Apri Kurniawan (Program Studi Pendidikan Matematika, 2023)
The purpose of this study was to test whether the Open-Ended approach with the Thinking Aloud Pair Problem Solving (TAPPS) strategy is effective in terms of learning achievement and curiosity of junior high school students. The difference between this research and previous studies is that in the use of an open-ended approach students are required to express their thoughts orally to their colleagues through the TAPPS strategy. The One Group Pretest Posttest Design was used in this quasi-experimental study. The research sample was selected using cluster random sampling, with this technique class IIC was selected as the sample class. Multiple choice questions were used in this study to see learning achievement and questionnaires were used to see curiosity. Proportions test, paired t-test, and one-sample t-test were used to evaluate effectiveness. The proportion test shows that for both learning achievement and curiosity while . Paired t-test showed for learning achievement and for curiosity while the one sample t-test showed for learning achievement and for curiosity. For the last two tests use . The criteria for the three tests are the same, that is, they are met if . Based on the results of statistical tests, it can be concluded that the Open-Ended approach with the TAPPS strategy is effective for students in terms of learning achievement and curiosity, according to hypothesis testing at a significance level of 5%.